Bids and Allocations in European IPO Bookbuilding. - Jenkinson, T; Jones, H (2004)
This paper uses evidence from a data set of 27 European IPOs to analyze how investors bid and the factors that influence their allocations. We also make use of a unique ranking of investor quality, associated with the likelihood of flipping the IPO. We find that investors perceived to be long-term holders of the stock are consistently favored in allocation and in out-turn profits. In contrast to Cornelli and Goldreich (2001), we find little evidence that more informative bids receive larger allocations or higher profits. Our results cast doubt upon the extent of information production during the bookbuilding period.